2009
DOI: 10.1021/ja906744r
|View full text |Cite
|
Sign up to set email alerts
|

Formal Alkyne Aza-Prins Cyclization: Gold(I)-Catalyzed Cycloisomerization of Mixed N,O-Acetals Generated from Homopropargylic Amines to Highly Substituted Piperidines

Abstract: A new gold(I)-catalyzed cycloisomerization to access highly substituted piperidines has been developed. By combining a conceptually new way of generating iminium ions using cationic gold(I) complexes and an efficient cyclization reaction that can minimize a potentially competing aza-Cope rearrangement, the proposed reaction successfully circumvents a long-standing problem in the classical aza-Prins reaction. Synthetic utility of the catalytic reaction was demonstrated by a synthesis of optically active 2-alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Taking benefit of residual Brønsted acidities remaining on hybrids, Blanc and co‐workers have also demonstrated the capacity of Au I /POM compounds to act as dual catalysts (Table ) . In a two‐step sequence, the cyclic enol ether 95 was generated from N , O ‐acetal 94 via an aza‐Prins cyclization using 10 mol % of the strongly electron withdrawing tri(pentafluorophenyl)phosphane gold(I) complex, and was subsequently hydrolyzed to furnish the ketone 96 (Table , entry 1) . With Au I /H + /POM, the product 96 was obtained in a one‐step procedure with only 2.5 mol % of catalyst loading in the same reaction conditions (67–89 %, Table , entries 2–7).…”
Section: Applications In Gold Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Taking benefit of residual Brønsted acidities remaining on hybrids, Blanc and co‐workers have also demonstrated the capacity of Au I /POM compounds to act as dual catalysts (Table ) . In a two‐step sequence, the cyclic enol ether 95 was generated from N , O ‐acetal 94 via an aza‐Prins cyclization using 10 mol % of the strongly electron withdrawing tri(pentafluorophenyl)phosphane gold(I) complex, and was subsequently hydrolyzed to furnish the ketone 96 (Table , entry 1) . With Au I /H + /POM, the product 96 was obtained in a one‐step procedure with only 2.5 mol % of catalyst loading in the same reaction conditions (67–89 %, Table , entries 2–7).…”
Section: Applications In Gold Catalysismentioning
confidence: 99%
“…[30] In at wo-step sequence, the cyclic enol ether 95 was generated from N,O-acetal 94 via an aza-Prins cyclization using 10 mol %o ft he strongly electron withdrawing tri(pentafluorophenyl)phosphaneg old(I) complex, and was subsequently hydrolyzed to furnish the ketone 96 (Table6,e ntry 1). [49] With Au I /H + /POM, the product 96 was obtained in ao ne-step procedure with only 2.5 mol %o fc atalystl oading in the same reactionconditions (67-89 %, Ta ble6,e ntries 2-7). Interestingly, similar and even better yields were achieved with the Au I /POM compared to the homogeneous version.…”
Section: Entry 16-enyne Time [H]mentioning
confidence: 99%
“…Aw ide variety of transformations have been devised that employt hese substrates, which give access to severaln itrogen-containing heterocycles. [9] However, to date, substrates bearing aq uaternary stereocenter have not yet been tested. In the contexto fa no ngoing project in our labo- ratory,w ee valuated the reactivity of protected quaternary homopropargylic amino esters under gold catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been known for a long time that allyl alcohols undergo intermolecular alkoxylation-[3,3]-sigmatropic rearrangement under Ag(I) or Au(I) catalysis [78], allyl ethers that are less nucleophilic due to steric reasons react more slowly and have not been known to undergo similar reactions until recently. In our previous work [9], it was shown that ester-substituted alkynes underwent an efficient intermolecular carboalkoxylation with allyl ethers via a tandem conjugate addition and a [3,3]-sigmatropic rearrangement [1012]. Preliminary results in the above studies [5,9] have demonstrated that a polarizing effect of the sulfonyl substituent on the alkyne is highly effective in promoting the reaction under a mild condition with relatively low amount of excess reactants.…”
Section: Introductionmentioning
confidence: 99%